Model Pembelajaran Problem Base Learning (PBL) untuk Berpikir Kritis Siswa (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2025)
Critical thinking skills are considered a fundamental skill essential for facing the challenges and complex issues of the 21st century. One teaching strategy considered effective in fostering these skills is the Problem-Based Learning (PBL) method. This study aims to describe the application of PBL in the teaching and learning process and its impact on strengthening students' critical thinking skills. The approach used in this research is classroom action research (CAR) with descriptive qualitative methods. The study results revealed that the use of PBL can improve students' critical thinking skills, particularly in the aspects of interpretation, analysis, and assessment. In addition, the implementation of PBL also has a positive impact on increasing student activeness, collaboration skills, and independence in the learning process. Obstacles encountered during the learning process can be minimized through the application of appropriate strategies, such as providing scaffolding and optimizing the use of digital-based learning resources. These findings make an important contribution to the development of more effective teaching methods in improving the quality of students' critical thinking in schools, as well as offering practical solutions for teachers to increase student engagement in problem-based learning.